1247 Fusobacterium Necrophorum - A Rare Thyroglossal Cyst Habitat That Can Be Lethal. (12th October 2021) - Goel, A; Oikonomou, C; Amini, A
Abstract: Thyroglossal cyst is the most frequent developmental cervical anomaly with a prevalence of 7% in the population. Infection and abscess formation are common complications. Isolation of Fusobacterium Necrophorum (F. Necrophorum) made the management of this case challenging. An 18-year-old male presented to the emergency department with a 3-day history of a neck mass, sore throat, cachexia, dysphagia and fever. Clinical examination revealed an erythematous 4 x 5 fluctuant swelling in the midline of the neck with evident lymphadenopathy on level II on the left-hand side. A CT neck that was undertaken nine months ago was suggestive of a thyroglossal cyst and the patient was placed in the waiting list for surgical excision under general anaesthesia. He reported three episodes of midline neck swelling since then. Upon admission, ultrasound guided drainage was arranged, and a pus sample obtained. The presence of F. Necrophorum was reported by microbiology with instructions of urgent admission and strict antibiotic regime. Excision of the cyst was scheduled after the completion of the antibiotic course. Fusobacterium Necrophorum is a rare microorganism with increased virulence and a significant mortality rate. It has been involved in oropharyngeal infections complicated by Lemierre's syndrome, necrobacillosis, post anginal sepsis and septic jugular thrombophlebitis making this case of particular interest.